RELIGION AS A MEANS OF RESTORATION: A THEOLOGICAL APPROACH TO TRAUMA AND RELIGIOUS VIOLENCE IN INDONESIA - Zulkarnain Zulkarnain (Manna Rafflesia, 2025)
This article advocates for a constructive theological approach, in which theology is employed to interpret and give meaning to human experiences within the public sphere and daily life. One of the most profound traumatic experiences faced by individuals and societies is violence. Religious violence, in particular, represents a collective trauma, as it involves the misuse of religious symbols and language to legitimize acts of aggression. Consequently, theological efforts are essential to rediscover and reaffirm the noble values that constitute the essence and true purpose of religion, ensuring their revitalization. Importantly, the phenomenon of violence perpetrated in the name of religion does not indicate that religion itself is inherently violent; rather, it underscores the propensity of certain religious adherents toward conflict and aggression. This article also seeks to challenge and correct the stigmatization imposed by secularist perspectives, which unjustly portray religion as a fundamental source of violence, as a dangerous entity, or as a force that contributes more to harm than to good. On the contrary, this study highlights the richness of religious traditions, which encompass profound teachings of virtue, nobility, and moral greatness—values that hold significant potential for fostering healing, peace, solidarity, and reconciliation. Furthermore, this article explores the necessity of religious engagement in contemporary global and pluralistic societies. It examines how religious communities should embody their theological commitments within the public sphere in ways that contribute to minimizing human suffering and addressing the traumas that pervade modern life .